The Games people play : theology, religion and sport - Ellis, Robert (Robert Anthony) ([Place of publication not identified] : Wipf & Stock Publishers, 2014)
In 'The Games People Play', Robert Ellis constructs a theology around the global cultural phenomenon of modern sport, paying particular attention to its British and American manifestations. Using historical narrative and social analysis to enter the debate on sport as religion, Ellis shows that modern sport may be said to have taken on some of the functions previously vested in organized religion. Through biblical and theological reflection, he presents a practical theology of sport's appeal and value, with special attention to the theological concept of transcendence. Throughout, he draws on o.
Why Play Sport? Sociocultural FactorsWhy Play Sport? Sport and "Religious Experience"; Why Winning Matters; Deus Ludens, Deus Victor: God the Winner; 6. "To Boldly Go": Sport as Divine Encounter?; Imago Dei: Further Thoughts; Transcendence and the Transcendent; Vicarious Sport; Sin and Salvation in Sport?; Conclusion: "The Theology Behind All Cultural Expressions"; Highlights; Some Loose Ends; Concluding Observations on a Practical Theology of Sport; Bibliography; Back cover.
Print version record.
Includes bibliographical references.
OCLC control number change
Keywords: Sports -- Religious aspects; Sports -- Moral and ethical aspects; Competition (Psychology); GAMES / Gambling / Sports; SPORTS & RECREATION / Business Aspects; SPORTS & RECREATION / Essays; SPORTS & RECREATION / History; SPORTS & RECREATION / Reference; TRAVEL / Special Interest / Sports; Competition (Psychology); Sports -- Moral and ethical aspects; Sports -- Religious aspects; Competition (Psychology); Sports -- Moral and ethical aspects; Sports -- Religious aspects; Electronic books; Electronic books